Processos formativos na escola e a construção de matrizes pedagógicas coletivas - Nhoque, Janete Ribeiro (2010)
This work investigates as may be welcome as manifestation of teachers’ pedagogical bases in educational spaces, considering the organizational context in which they were in. It results from a qualitative research whose data were produced from the analysis of the transcripts of ten meetings with two groups of teachers while formation of a public school of Sao Paulo. That have been established for dialogue with theoretical scholars who investigate training of teachers and authors to investigate the establishment and operation of groups.Teacher education is a complex issue which has changed its focus from the eighties, a vision of the teacher as a technician, a mere transmitter and receiver of knowledge previously elaborated to a vision that recognizes that teachers can be producers of knowledge and puts them in the spotlight. In this perspective, the school becomes the prime location for training. Research shows that training in the school occurs in groups and work with these groups requires the trainer's care and attention, because these groups have a common social imaginary which can often involve the trainer on his "symbolic frame" and the training may not succeed. The development of this work enabled some inferences: The school is complex and life and death pass through in their daily lives, leaving marks that remain in memory, the memories. These groups that make up the school is often organized around idealizations , illusions and beliefs that guide the action of the teacher and their relationship with students and their families and end up causing tensions in these relationships. The teachers, when provoked, talk about their experiences of life and school, the narrative approaches and establishes ties of friendship and deep insights into the possibilities and reflection on their teaching, and finally it is possible to build the school educational spaces where teachers take their training and knowledge to produce, making it necessary to give voice to these teachers, encouraging those who develop projects of interest to students and the community in line with school projects, putting in movement the pedagogical bases.